STEM-20. THE ROLE OF HUMAN BETA DEFENSINS IN THE CLONOGENICITY OF GLIOBLASTOMA MULTIFORME. (12th November 2021) - Harris, Peggy; Kerstetter-Fogle, Amber; Sloan, Anthony; Raghavan, Alankrita; Hoffman, Harry; Barnholtz-Sloan, Jill; Couce, Marta; Jin, Ge; Weinberg, Aaron; Sloan, Andrew
Abstract: INTRODUCTION: Glioblastoma (GBM) is the most common primary malignant brain tumor with a median overall survival of 12-15months. GBM aggressiveness and poor response to treatment are often attributed to a small population of stem-like cells referred to as glioma stem cells (GSCs). Human Beta-Defensins (HBDs), a family of small molecules initially thought to function as anti-microbials, have been implicated in various cancers with functions that are cancer type specific, including proinflammatory and immunosuppressive roles. GOAL: This study aimed to elucidate HBDs expression in GSCs and differentiated gioma cells (DGSs). METHODS: We identified HBD2 and HBD3 in glioma and GSCs and DGSs by immunofluorescence (IF) and immunohistochemistry (IHC). We also assessed the role HBD2/3 play in GBM oncogenesis by investigating their effects on the self-renewal capacity of GSCs. RESULTS: HBD2 and HBD3 are found in both bulk tumor and GSCs by IHC and IF. Expression of HBD2 and HBD3 mRNA levels are elevated in GBM patient tissue in comparison to lower grade gliomas by 16.2 & 1.9 fold (respectively; p < 0.0001). Additionally, transcriptional expression of HBD2 and HBD3 are increased by 0.68 and 1.15 fold respectively in GSCs versus autologous DGCs (p < 0.05; p< 0.005 respectively), suggesting a role for HBD 2/3 in oncogenesis. Interestingly however, HBD2 and HBD3 pretreatment of GSC cell lines showed decreased self-renewal capacity by 34.2 and 66.4% (p < 0.001), determined by the reduced number of large neurospheres ( >250mm). CONCLUSIONS: Our results demonstrate the presence of HBD2/3 in GBM samples by IHC and IF with increased HBD2/3 mRNA expression in GBM samples. Interestingly DGCs contain less HBD2/3 than their GCS counterparts, and clonogenicity assays demonstrate a decrease in oncogenesis, suggesting that HBD's role in proliferation and clonogenicity of DGCs and GSCs may be context dependent, leading to additional questions and future studies.